The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.26650/jot.2019.5.2.0032
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Museums for Visually Impaired: A Case Study from Istanbul

Abstract: Freedom to travel is a fundamental human right. Thus, disabled people should be able to travel. Disabilities are divided into subcategories, whereby vision disability is one of them. In the context of museums, there are some implementations for visually disabled people. However, there is still limited empirical investigation on the expectations, satisfaction, and challenges of visually impaired travelers. Therefore, the purpose of this study is to determine the expectations, needs, and challenges of visually i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…At this point, the views in the studies also supported this finding. Studies mentioned that it was important to create virtual museums that contain the collections in order to ensure that museum collections can be accessed under equal conditions for all individuals in the society from every place and environment (Dincer et al, 2019). Again, within the scope of the first sub-goal, the participants associated the concept of accessible museum with museum architecture and the presentation of equal opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At this point, the views in the studies also supported this finding. Studies mentioned that it was important to create virtual museums that contain the collections in order to ensure that museum collections can be accessed under equal conditions for all individuals in the society from every place and environment (Dincer et al, 2019). Again, within the scope of the first sub-goal, the participants associated the concept of accessible museum with museum architecture and the presentation of equal opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with the views in the literature. In the literature, it was stated that objects that represent a combined or original work for visually impaired individuals are needed (Yesilyurt, 2014), and audio guide systems are important for disabled individuals to experience museum visits (Dincer et al, 2019). In addition, it was mentioned in the literature that mobile devices had an important place in the lives of individuals, and it was seen as one of the most important applications for all individuals to gain experience with museums and integrating museums with technology (Akca, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the priority needs for museum visitors who are BPS were (a) exhibitions and collections accessible, for example, tactilely or auditorily, and (b) assistance and interpretation by museum staff and volunteers. Istanbullu Dincer et al [ 8 ] aimed to identify the needs, challenges, and satisfaction level of people who are BPS during museum visits. Findings showed that participants generally mentioned problematic accessibility issues such as the lack of multisensory experiences, that is, tactile, auditory, and olfactory access; the lack of arrangements allowing a museum visit without a companion; and the participants’ expectations regarding the alleviation of these issues.…”
Section: Related Workmentioning
confidence: 99%